Local Web Based Internal Corporate Meals Request System With Email Approval Using ASP.Net MVC - Williem Williem; Amroh Lutfiah Adila (President University, 2023)
Indonesia is one of the countries with the largest manufacturing industry in the world. Manufacturing companies in Indonesia have many workers who work hand in hand to build a better industry with meetings, training, kaizen, and others. The activities of the company require a consumption ordering system to support the sustainability of the activities of the manufacturing company. Most manufacturing companies still use a manual ordering system, namely by filling out the order form with Microsoft Excel and calling the canteen vendor who takes care of ordering food to order via WhatsApp message to the email. This causes a lot of time wasted on ordering food, late billing, to over budget which makes the company must spend more funds than before. Therefore, this final project discusses the creation of a website-based consumption ordering system application with an approval feature through email, which is expected to help overcome problems that have been occurring in manufacturing companies. So that the consumption ordering process can be well integrated, systematic, and reduce the possibility of errors that occur to cause losses.